Single bubble rise in GaInSn in a horizontal magnetic field. (July 2018) - Richter, T.; Keplinger, O.; Shevchenko, N.; Wondrak, T.; Eckert, K.; Eckert, S.; Odenbach, S.
Highlights: The rise of single argon bubbles in liquid GaInSn is studied by the ultrasound transit time technique. Trajectories and horizontal velocity of the bubbles are measured as a function of the magnetic field. A new initial path instability of the zig-zag trajectory was observed. At the initial path instability, a deceleration of the bubble and a strong tilt of its axis occurs. Abstract: The rise of single gas bubbles of moderate size ( ∼ 5 mm) in a liquid metal was studied in a flat container filled with the eutectic alloy GaInSn. The bubble motion is affected by a homogeneous horizontal magnetic field which is perpendicular to the width side of the fluid container. Measurements of the bubble trajectory, bubble velocity and deformation were performed by means of a combination of ultrasound transit time technique and X-ray radiography. In the hydrodynamic case without a magnetic field, the bubbles show the typical zigzag movement whose attenuation can be observed for sufficiently high magnetic fields of B > 270 mT. The bubble trajectory becomes straight at a field strength of about 500 mT. A damping of the zigzag path does not result in case of small magnetic fields applied. In this parameter range, even an increase of the amplitude of the lateral path oscillation is observed. Furthermore, this study revealed a discontinuity in the bubble path, which is called as "initial path instability" on the basis of its occurrence in the early stage of the bubble rise shortly after the bubble injection. This instability is characterized by an extreme inclination of the ellipsoidal bubble which often leads to a bubble "somersault". This instability is suppressed by a sufficiently high enough magnetic field. The reason for this instability and the magnetic field effect thereon are qualitatively discussed.